Antibacterial activity of ethanolic extract of leaves and bulbs of Crinum asiaticum L. against acne-inducing bacteria - Azrifitria .; Syaikhul Aziz; Chairul . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
The antibacterial activity of ethanolic extract of leaves and bulbs of Crinum asiaticum L. was tested against Propionibacterium acnes, Staphylococcus aureus and Staphylococcus epidermidis, pathogenic bacteria that cause acne. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined by dilution methods. MIC and MBC of ethanol leaves extract were found for P. acnes (1.25 and 2.5 mg/mL), S. aureus (5 and 10 mg/mL) and S. epidermidis (2.5 and 5 mg/mL). While MIC and MBC of ethanol bulbs extract were found for P. acnes (7.5 and 15 mg/mL), S. aureus (7.5 and 15 mg/mL) and S. epidermidis (3.75 and 7.5 mg/mL). Further study conducted on the ethanol leaves extract against P. acnes to analyze cell leakage (nucleic acid and protein) by ultraviolet spectrophotometry, metal ion (K+ and Ca2+) by atomic absorption spectrometry, and observed alteration of the cell wall by scanning electron microscopy (SEM). The result showed that ethanol leaves extract could damage the cell wall and affect the permeability of cell membrane which marked by release of nucleic acid (absorbance 0.3307-0.4299), protein (absorbance 0.0616-0.101), ion K+ (8.167-15.757 mg/mL), ion Ca2+ (5.47-13.74 mg/L) from the cell and alter morphology of cell wall of P. acnes.Key words: Antibacterial, Crinum asiaticum L., Propionibacterium acnes